2017
DOI: 10.21037/cdt.2017.08.09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of chronic kidney disease in a group of patients with hypertension in the Savanah zone of Cameroon: a cross-sectional study in Sub-Saharan Africa

Abstract: The prevalence of CKD in adults with hypertension was high. This was associated with age greater than 50 years, female sex, obesity and the hyperuricemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
3
20
1
1
Order By: Relevance
“…About a third to half of patients with hypertension in Cameroon had CKD [27] which varied from that which Bahrey et al reported (about 1 in 5 hypertensives) in Ethiopia [51]. This discrepancy can be attributed to the difference in study population as the latter study was performed in North Africa.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…About a third to half of patients with hypertension in Cameroon had CKD [27] which varied from that which Bahrey et al reported (about 1 in 5 hypertensives) in Ethiopia [51]. This discrepancy can be attributed to the difference in study population as the latter study was performed in North Africa.…”
Section: Discussionmentioning
confidence: 81%
“…Search terms #1 "Kidney disease*" OR "kidney failure" OR "Renal disease" OR "Renal insu ciency" OR "Chronic kidney" OR "Chronic renal" OR "CKD" OR "CKF" OR "CRD" OR "end-stage renal" OR "end-stage kidney" OR "endstage renal" OR "endstage kidney" OR "uremia" OR "uraemia" OR "dialysis" OR "hemo ltration" OR "haemo ltration" OR "hemodia ltration" OR "haemodia ltration" OR "hemodialysis" OR "haemodialysis" OR "renal dialysis" Prevalence of CKD in Cameroon Table 2 summarizes the studies that reported on the prevalence of CKD in Cameroon. The prevalence of CKD was reported in 11 studies in Cameroon [11,17,[24][25][26][27][28][29][30][31][32]. All studies were cross-sectional studies, 4 (36.4%) were community-based, and 2 (18.2%) were conducted in rural areas.…”
Section: Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghana [12], in Sub-Saharan Africa [13], Democratic Republic of Congo [14] and Nigeria [15] (31%) ,47%…”
Section: Discussionmentioning
confidence: 99%